2007
DOI: 10.1093/nar/gkl1144
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the U1 snRNP of Schizosaccharomyces pombe reveals three essential organism-specific proteins

Abstract: Characterization of spliceosomal complexes in the fission yeast Schizosaccharomyces pombe revealed particles sedimenting in the range of 30–60S, exclusively containing U1 snRNA. Here, we report the tandem affinity purification (TAP) of U1-specific protein complexes. The components of the complexes were identified using (LC-MS/MS) mass spectrometry. The fission yeast U1 snRNP contains 16 proteins, including the 7 Sm snRNP core proteins. In both fission and budding yeast, the U1 snRNP contains 9 and 10 U1 specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…In F. graminearum , 139 genes had at least one intron with altered splicing efficiency in the Fgsrp1 deletion mutant. One (FGRRES_01244) of these genes with splicing efficiency defects is orthologous to PRP39 that is an essential component of yeast spliceosome (Lockhart and Rymond, ; Newo et al ., ). Therefore, it is likely that FgSRP1 plays a role in intron splicing in F. graminearum .…”
Section: Discussionsupporting
confidence: 78%
“…In F. graminearum , 139 genes had at least one intron with altered splicing efficiency in the Fgsrp1 deletion mutant. One (FGRRES_01244) of these genes with splicing efficiency defects is orthologous to PRP39 that is an essential component of yeast spliceosome (Lockhart and Rymond, ; Newo et al ., ). Therefore, it is likely that FgSRP1 plays a role in intron splicing in F. graminearum .…”
Section: Discussionsupporting
confidence: 78%
“…The role of Snu71 remains elusive too. Newo et al [ 32 ] have analyzed the U1 snRNP of Schizosaccharomyces pombe and found no homolog of Snu71 although homologs of Prp40 and Luc7 were clearly present. However, they speculate that Usp107p may be a functional homolog of Snu71, given its similar size and the presence of a PWI domain in Usp107p.…”
Section: Discussionmentioning
confidence: 99%
“…Fission yeast strains expressing TAP-Rrn7 and HA-Rrn11 were constructed as described in Newo et al (22).…”
Section: Methodsmentioning
confidence: 99%